Hierarchical MoS2/Polyaniline Nanowires with Excellent Electrochemical Performance for Lithium‐Ion Batteries. (11th December 2012) - Yang, Lichun; Wang, Sinong; Mao, Jianjiang; Deng, Junwen; Gao, Qingsheng; Tang, Yi; Schmidt, Oliver G.
<x xml:space="preserve">Abstract</x> Hierarchical MoS2/polyaniline nanowires, integrating MoS2 nanosheets with conductive polyaniline, serve as prominent anode materials for Li‐ion batteries, presenting high capacity and good cyclability. The polyaniline‐hybrid structure and hierarchical features significantly promote the Li‐storage performance as compared with the bare MoS2, indicating new opportunities for developing electrode nanomaterials. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>